Supporting Early Scientific Thinking Through Curiosity - Jirout, Jamie J. (Frontiers in Psychology, 2020)
Curiosity and curiosity-driven questioning are important for developing scientific thinking and more general interest and motivation to pursue scientific questions. While we know quite a bit about the development of children’s information seeking and question asking, we know much less about the development of curiosity. This perspective piece begins with a discussion of the role of curiosity in scientific thinking and what this looks like in early childhood, with an explanation for how curiosity can support scientific thinking. The article then describes several methods of promoting curiosity in early childhood based on a recent school-based framework. Finally, potential directions for research to address related questions of the development of curiosity and curiosity-driven inquiry in young children are discussed.